Recognizing the Martuwarra's First Law Right to Life as a Living Ancestral Being. Issue 3 (14th November 2020) - RiverOfLife, Martuwarra; Poelina, Anne; Bagnall, Donna; Lim, Michelle
Abstract: Traditional custodians of the Martuwarra (Fitzroy River) derive their identity and existence from this globally significant river. The First Laws of the Martuwarra are shared by Martuwarra Nations through a common songline, which sets out community and individual rights and duties. First Law recognizes the River as the Rainbow Serpent: a living ancestral being from source to sea. On 3 November 2016, the Fitzroy River Declaration was concluded between Martuwarra Nations. This marked the first time in Australia when both First Law and the rights of nature were recognized explicitly in a negotiated instrument. This article argues for legal recognition within colonial state laws of the Martuwarra as a living ancestral being by close analogy with the case concerning the Whanganui River. We seek to advance the scope of native title water rights in Australia and contend that implementation of First Law is fundamental for the protection of the right to life of the Martuwarra.